Combination drug therapy as a strategy to improve the efficacy and safety of treatment of herpes simplex virus infections: potential risks and prospects - Valeriya L. Andronova; Georgy A. Galegov (Вопросы вирусологии)
Herpes simplex viruses (HSV) are extremely widespread pathogens that cause human infections of varying severity, from mild orofacial ulcerations of the skin and mucous membranes to life-threatening encephalitis and severe generalized forms of infection or recurrent herpetic corneal lesions leading to blindness. Standard treatment with acyclovir, penciclovir, or the corresponding prodrugs valacyclovir and famciclovir is usually sufficient to stop recurrent HSV infections. However, immunocompromised patients are of particular concern and often require long-term antiviral therapy. In such conditions, the risk of developing drug resistance, often cross-resistance increases significantly, since all basic antiherpetic drugs have a similar mechanism of action and affect the same drug target – viral DNA polymerase (DNA-pol). With the development of drug resistance, the effectiveness of treatment decreases, and it becomes necessary to switch to second-line drugs with severe side effects. Thus, it is necessary to develop new alternative treatment options. The creation of drugs aimed at a biotarget different from DNA-pol eliminates the risk of cross-resistance to acyclovir and related drugs, and their use in combination with traditional antiherpetic drugs can prevent or slow down the development of drug resistance in the virus. When combining drugs that affect the pathogen in different ways, it is important to maintain the therapeutic effect with the use of lower doses due to the synergistic nature of the interaction, which reduces the likelihood of developing unwanted side effects of drugs. The review presents current data on the state and possible prospects for the development of combination therapy for HSV infections, obtained as a result of searching the literature related to anti-herpetical therapy using the PubMed, Medline databases, RSCI, the international registry of clinical trials of the US National Institutes of Health.